Preparation of Multiwall Carbon Nanotubes/Cellulose Nanocomposites Stabilized By 1-Butyl-3-Methyl-Imidazolium (BMIM) - Surfactants - Azoum Ali, Rabiaa Abu; Mohamed, Azmi (EDUCATUM Journal of Science, Mathematics and Technology, 2018)
Multiwall carbon nanotubes (MWCNTs) ability to improve electrical, optical and mechanical properties of nanocomposites, have attracted great amount of interest for their huge potential in applying them as filler in polymer matrix. However, this application was hindered because of their low dispersion in polymer matrix and tendency to self-associate into macro-scale aggregates. Recently, diffusion of MWCNTs in cellulose polymer matrix was studied and prepared via latex technology approaches by the addition of 1-butyl-3-methyl-imidazolium (BMIM)-surfactant. The performance of BMIM-surfactants for dispersing MWCNTs in polymer was characterized using a range of techniques including field emission scanning electron microscopy (FESEM), and Thermogravimetric analysis (TGA). Meanwhile, the conductivities of the nanocomposites were also investigated using four-point probe measurements. In this study, MWCNTs were efficiently dispersed in cellulose utilizing 1-butyl-3-methyl imidazolium-dodecyl benzene sulfonate (BMIM-DBS). Interestingly, it was found that BMIM-DBS performs much better than that of the commercially available surfactant sodium dodecyl benzenesulfonate (SDBS), demonstrating the importance of the effect of surfactant counter-ion leading to improved dispersion of MWCNTs in cellulose. This finding will significantly contribute towards the improvement of properties of cellulose for nanocomposite industries.